2019
DOI: 10.1111/pbi.13221
|View full text |Cite
|
Sign up to set email alerts
|

AKR2A participates in the regulation of cotton fibre development by modulating biosynthesis of very‐long‐chain fatty acids

Abstract: SummaryThe biosynthesis of very‐long‐chain fatty acids (VLCFAs) and their transport are required for fibre development. However, whether other regulatory factors are involved in this process is unknown. We report here that overexpression of an Arabidopsis gene ankyrin repeat‐containing protein 2A (AKR2A) in cotton promotes fibre elongation. RNA‐Seq analysis was employed to elucidate the mechanisms of AKR2A in regulating cotton fibre development. The VLCFA content and the ratio of VLCFAs to short‐chain fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…The identified DELs and DEGs in comparisons of 0 DPA vs -2 DPA and 5 DPA vs 0 DPA of ZM24 and fl indicated that many lncRNAs and coding genes are involved in the fiber initiation and primary development, while few lncRNAs and coding genes may involve the ovule development. The analysis of the DEGs further showed that fatty acid metabolism, very long strain fatty acid synthesis and sugar metabolism play important roles in the fiber initiation of ZM24, supporting the previous results [15,39]. Moreover, some MYB family, bHLH type TFs encoding genes were also identified the important roles in fiber initiation, which is in agreement with the function of these TFs in previous research [10,16,29,36,40,49,50].…”
Section: Discussionsupporting
confidence: 89%
“…The identified DELs and DEGs in comparisons of 0 DPA vs -2 DPA and 5 DPA vs 0 DPA of ZM24 and fl indicated that many lncRNAs and coding genes are involved in the fiber initiation and primary development, while few lncRNAs and coding genes may involve the ovule development. The analysis of the DEGs further showed that fatty acid metabolism, very long strain fatty acid synthesis and sugar metabolism play important roles in the fiber initiation of ZM24, supporting the previous results [15,39]. Moreover, some MYB family, bHLH type TFs encoding genes were also identified the important roles in fiber initiation, which is in agreement with the function of these TFs in previous research [10,16,29,36,40,49,50].…”
Section: Discussionsupporting
confidence: 89%
“…A previous study showed that the phenotypic changes of kcs1-1 mutants included relatively thin stems and reduced resistance to low-humidity stress at a young age 56 . Moreover, a recent study showed that the transcription of most lipid biosynthesis genes, such as KCS6 , increases during the rapid elongation stage and is maintained at a high level; moreover, the fatty acid biosynthetic pathway is also significantly induced in AKR2A-57 fibres 57 . In the present study, KCS-6 accumulation was downregulated, which indicated that tea plants could improve drought resistance by inhibiting the accumulation of KCS-6.…”
Section: Discussionmentioning
confidence: 99%
“…3 and 4 , Table S8). The biosynthesis of VLCFAs and their transport are required for fiber development (Hu et al 2007 ). The heterologous gene KCS of cotton expressed in Arabidopsis thaliana had promoted the elongation of stem cells (Qin et al 2007 ; Shi et al 2006 ).…”
Section: Discussionmentioning
confidence: 99%